Characterization of poly(L‐glutamic acid)‐grafted hyaluronan as a novel candidate medicine and biomedical device for intra‐articular injection. Issue 11 (9th August 2017) - Muramatsu, Kazuaki; Tajima, Yuya; Kaneko, Rin; Yanagita, Yuta; Hirai, Hiroyuki; Hiura, Nana
Abstract: A novel hyaluronan (HA) derivative, poly(L‐glutamic acid)‐grafted hyaluronan (PGA‐g‐HA), was synthesized to improve the durability of conventional HA products for intra‐articular injection. The purpose of this study was to investigate the characteristics of the novel HA derivative in terms of viscoelasticity, degradation behavior, non‐immunogenicity, and bioactivity using preliminary in vitro and in vivo experiments. The storage modulus ( G ′) and loss modulus ( G″ ) of PGA‐g‐HA were similar to those of HA80 (approximately 8.0 × 10 5 Da) rather than those of original HA200 (approximately 2.0 × 10 6 Da). PGA‐g‐HA showed strong resistance against hyaluronidase hydrolysis compared to unmodified HA200. The immunogenicity resulting from grafting PGA to HA200 was not detected in bone marrow derived dendritic cells. The anti‐inflammatory activity of PGA‐g‐HA was confirmed in IL‐1β‐stimulated chondrocytes. In addition, compared to unmodified HA200, the intra‐articular injection of PGA‐g‐HA produced greater chondroprotective effects on a monoiodoacetic acid‐induced model of rat knee osteoarthritis at two weeks after a single treatment. Therefore, PGA‐g‐HA is expected to be a promising medicine and biomedical device for intra‐articular injection. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3006–3016, 2017.